CARACTERIZAÇÃO DAS CONDIÇÕES DE SAÚDE DOS TRABALHADORES RURAIS DO MUNICÍPIO DE IJUÍ-RS - MARCHI, DIONE D.; CASALINI, ELENISE D. B.; BATTISTI, IARA E.; REIS, MAGDA C. T.; MATTE, ROSANA A. R.; BIGOLIN, MONE E. (Salão do Conhecimento, 2013)
Resumo